2016
DOI: 10.5312/wjo.v7.i1.38
|View full text |Cite
|
Sign up to set email alerts
|

Direct anterior total hip arthroplasty: Literature review of variations in surgical technique

Abstract: The direct anterior approach to the hip has been suggested to have several advantages compared to previously popular approaches through its use of an intra-muscular and intra-nervous interval between the tensor fasciae latae and sartorius muscles. Recent increased interest in tissue-sparing and minimally-invasive arthroplasty has given rise to a sharp increase in the utilization of direct anterior total hip arthroplasty. A number of variations of the procedure have been described and several authors have publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 28 publications
0
35
0
2
Order By: Relevance
“…After the iliofemoral ligament and the anterior articular capsule be revealed in a DAA, many surgeons open the anterior capsule in a "T" or transverse fashion to expose the hip joint and later close the capsule by suture or not close the capsule after the arthroplasty; both closing or not closing the capsule are widely accepted [5,[18][19][20][21][22]. Although some surgeons believe that the anterior capsule is not important, we have found a new application for this structure.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…After the iliofemoral ligament and the anterior articular capsule be revealed in a DAA, many surgeons open the anterior capsule in a "T" or transverse fashion to expose the hip joint and later close the capsule by suture or not close the capsule after the arthroplasty; both closing or not closing the capsule are widely accepted [5,[18][19][20][21][22]. Although some surgeons believe that the anterior capsule is not important, we have found a new application for this structure.…”
Section: Introductionmentioning
confidence: 94%
“…This approach is favored by surgeons, because it utilizes the intermuscular plane, thereby avoiding the need to transect any of the periarticular muscles. Moreover, this approach is favored because it provides adequate exposure of the acetabular side [1][2][3][4][5]. Several studies have reported that DAA decreases the duration of hospital stay and increases the percentage of patients discharged home due to the lesser operative trauma which permits a more rapid recovery [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…This approach increases the risk of nerve damage and may not be suitable for certain patient's anatomy because of the limited access to the posterior column. 6…”
Section: Possible Complicationsmentioning
confidence: 99%
“…Moreover, this approach is favored because it provides adequate exposure of the acetabular side. [1][2][3][4][5] Several studies have reported that DAA decreases the duration of hospital stay and increases the percentage of patients discharged home due to the lesser operative trauma which permits a more rapid recovery. [5][6][7][8][9] Whether DAA is actually superior to other surgical approaches, however, remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Several studies have reported that DAA decreases the duration of hospital stay and increases the percentage of patients discharged home due to the lesser operative trauma which permits a more rapid recovery. [5][6][7][8][9] Whether DAA is actually superior to other surgical approaches, however, remains controversial. Due to some concerns of less adequate exposure caused by difficulty elevating of proximal femur, some complications can occur during the operation, such as contusion of periarticular muscles, injury to the anterolateral femoral cutaneous nerve, and fractures around the prosthesis.…”
Section: Introductionmentioning
confidence: 99%